2008
DOI: 10.1007/s10532-008-9206-2
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation kinetics of trans-4-methyl-1-cyclohexane carboxylic acid

Abstract: Naphthenic acids are a complex mixture of organic compounds which naturally occur in crude oil. Low molecular weight components of the naphthenic acids are known to be toxic in aquatic environments and there is a need to better understand the factors controlling the kinetics of their biodegradation. In this study, a relatively low molecular weight naphthenic acid compound (trans-isomer of 4-methyl-1-cyclohexane carboxylic acid) and a microbial culture developed in our laboratory were used to study the biodegra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 14 publications
3
15
1
Order By: Relevance
“…4). In the previous biodegradation studies on other contaminants, a similar trend in biomass yield was observed (Lee et al 1993;Paslawski et al 2009). Lee et al (1993) demonstrated that the substrate can penetrate into the cell membrane and interact with microbial membrane proteins, causing the proteins to malfunction and reducing the biomass yield.…”
Section: Effect Of Initial Diesel Concentrationsupporting
confidence: 78%
“…4). In the previous biodegradation studies on other contaminants, a similar trend in biomass yield was observed (Lee et al 1993;Paslawski et al 2009). Lee et al (1993) demonstrated that the substrate can penetrate into the cell membrane and interact with microbial membrane proteins, causing the proteins to malfunction and reducing the biomass yield.…”
Section: Effect Of Initial Diesel Concentrationsupporting
confidence: 78%
“…Variovorax gradually became dominant as incubation time increased. This genus is able to biodegrade carboxylic acids (Paslawski et al, 2009), along with a variety of recalcitrant organics, such as atrazine, nitrotyrosine, 2,2′-dithiodibenzoic acid, 3-(3,4-dichlorophenyl)-1-methoxy-1-methylurea and acyl-homoserine lactones (Jamieson et al, 2009;Young et al, 2006). Another potentially important strain was Methylobacterium, which can consume used engine oil (contains aliphatics, aromatics and branched alkanes), aldehydes and nitroaromatics (Qiu et al, 2014;Salam et al, 2015;Van Aken et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Studies using model compounds (chemically synthesized in the laboratory) and commercial compounds (derived during petroleum fractionation) have provided an insight into the NA metabolic pathways (Rho and Evans, 1975;Taylor and Trudgill, 1978;Clemente et al, 2004;Smith et al, 2008). On the basis of these findings, biodegradation is affected by chemical structure (Whitby, 2010): generally, the more recalcitrant NAs have high molecular weights, contain multiple branched alkyl chains and methyl substituted cycloalkane rings Paslawski et al, 2009;Videla et al, 2009). Although methyl groups hinder NA biodegradation (Herman et al, 1993;Smith et al, 2008), mixed bacterial populations can degrade NAs with methyl substitutions on the cycloalkane rings (Herman et al, 1993;Headley et al, 2002a, b;Smith et al, 2008), demonstrating the importance of microbial consortia for complete NA biodegradation.…”
Section: Introductionmentioning
confidence: 99%